Polarization effects in the simulation of lead (II) fluoride - Castiglione, M; Wilson, M; Madden, P (1999)
An interionic potential to describe the interactions in PbF2 is constructed from ab initia calculations. The potential is based upon formal ionic charges and includes polarization effects arising from the induced dipoles on both anions and cations. The cation polarization effects are shown to be crucial to explain observable differences between PbF2 and alkaline-earth fluorides of comparable cation size (SrF2 and BaF2). In particular, the lower transition pressure between the β-(fluorite) and α-(cotunnite) phases and the qualitative difference between the shapes of the phonon dispersion for FbF2 and the alkaline earths are reproduced. Simulations show a transition to a superionic conducting state in the β-phase, though at a temperature slightly higher than that observed experimentally. No ionic conduction is observed in the α-phase at comparable temperatures, in agreement with experiment. The pattern of diffuse neutron scattering predicted by the simulations in the superionic domain is shown to reproduce the distinctive distribution of intensity observed experimentally.